Tight relationships between leaf and topsoil stoichiometries after 42 years of forest conversion from old-growth forests to Chinese fir plantations - Zhang, Cancan; Li, Yuxin; Li, Xin; Chen, Fusheng; Jin, Zhifang; Li, Yaoqi; Ma, Yaohua; Zeng, Shiqi; Yang, Shiyun; Bu, Wensheng (Frontiers in Forests and Global Change, 2023)
Soil C:N:P stoichiometry can regulate plant survival and reflect soil fertility and nutrient utilization. Despite the widespread conversion of old-growth forests to plantations or secondary forests, there is little knowledge about how these conversions affect the relation between leaf and soil stoichiometries. We examined the topography, leaf, and soil stoichiometries of 75 plots (20 m × 20 m) across Chinese fir plantations, secondary forests, and old-growth forests in subtropical China. We found that: (1) there were significant differences in leaf carbon, nitrogen, phosphorus, and their stoichiometry ratios among different stand types; (2) stand type significantly affected soil SOC, TP, C:N, C:P, and N:P, except TN; (3) the explanation percentage of leaf stoichiometry on soil stoichiometry doubled with the conversion of old-growth forest to Chinese fir plantation, whereas it was twofold decreased with the conversion of old-growth forest to secondary forest; The explanation percentage of topography on soil stoichiometry decreased onefold at a minimum with the conversion of the old-growth forest to the Chinese fir plantation or the secondary forest. Our results show the shortages of soil nutrients from transforming old-growth forests into plantations or secondary forests and indicate the urgent need to preserve the remaining old-growth forests and increase stand ages by reducing forest disturbances.Therefore, determining the optimal stand type and slope location can effectively promote the accumulation of carbon, nitrogen, and phosphorus nutrients in the topsoil, which is essential for improving the planning and implementation of appropriate forest restoration and ecosystem management strategies.